IgG4-related disease-like lesion arising within a well-differentiated liposarcoma/an atypical lipomatous tumor: two cases report - Oike, Naoki; Torigoe, Tomoaki; Ogose, Akira; Ariizumi, Takashi; Miyazaki, Tomohiro; Murayama, Yudai; Homma, Taku; Umezu, Hajime; Watanabe, Takuya; Kawashima, Hiroyuki (Frontiers in Oncology, 2025)
IntroductionWell-differentiated liposarcoma (WDLPS) is a locally aggressive soft tissue sarcoma characterized by the amplification of MDM2 and/or CDK4. IgG4-related disease (IgG4-RD) is a rare fibroinflammatory disease characterized by elevated serum IgG4 levels and histologically fibrous tissues with IgG4-positive immune cell infiltration. Although IgG4-RD often mimics other diseases, including malignant neoplasms, the association between IgG4-RD and WDLPS has not been fully elucidated. Here, we present two cases of IgG4-RD occurring within WDLPS.Case presentationA 56-year-old man presented with a left retroperitoneal mass, and a 64-year-old woman presented with a non-tender mass in her right thigh. Magnetic resonance imaging revealed that the tumors were composed of adipose and non-adipose areas with homogeneous enhancement. A biopsy revealed that the tumor consisted of adipose cells of various sizes and fibrous tissue with IgG4-positive cell infiltration. MDM2 amplification was detected using fluorescence in situ hybridization in both the adipose and fibrous areas. In addition, serum IgG4 levels were elevated in both patients, and IgG4-RD within the WDLPS were diagnosed. Wide resection was performed as radical treatment. After resection, the serum IgG4 level decreased to normal. No recurrence or metastasis has been observed for >19 months.ConclusionOur cases highlight the importance of careful biopsy for the accurate diagnosis of patients with IgG4-RD within WDLPS. Moreover, although the main treatment for IgG4-RD is systemic corticosteroids, IgG4-RD within WDLPS should be treated with surgical resection.